The Thermal and Structural Analysis of Vertical Stability Coil - Wang, Xianewei; Han, Peng; He, Qing; Li, Xiulian (Manufacturing Technology Journal, 2020)
The vertical stability coil is a new set of saddle shaped non-superconducting coil designed for the purpose of improving the control capability of plasma vertical movement. To avoid the electromagnetic shielding and en-hance the response performance, the vertical stability coil is installed in the inner wall of vacuum vessel. The subsequent disadvantage accompanying the benefit is that the coil is under severe neutron radiation. Besides the neutron radiation the coil will also encounter the ohmic heat once it is energized. The temperature rising of vertical stability coil is not allowed to beyond the specific threshold to guarantee the reliability of the coil com-ponents. Thus, the ohmic heat and nuclear heat calculation methods are presented and the detail temperature field is analysed by using ANSYS to check whether or not the coil can bear the thermal load. In addition, the thermal load will result in the thermal stress. To verify whether the thermal stress will lead to the structural damage, the thermal-structural coupling analysis is launched and the stress is evaluated based on ASME ana-lytical design. The analysis results will provide guidance for the local structural optimization of vertical stabil-ity coil.
Keywords: Vertical stability; Ohmic heat; Nuclear heat; Stress evaluation